An AP‐3‐dependent pathway directs phagosome fusion with Rab8 and Rab11 vesicles involved in TLR2 signaling. (24th October 2022) - Petnicki‐Ocwieja, Tanja; Sharma, Bijaya; Powale, Urmila; Pathak, Devesh; Tan, Shumin; Hu, Linden T.
Abstract: Intracellular compartmentalization of ligands, receptors and signaling molecules has been recognized as an important regulator of inflammation. The toll‐like receptor (TLR) 2 pathway utilizes the trafficking molecule adaptor protein 3 (AP‐3) to activate interleukin (IL)‐6 signaling from within phagosomal compartments. To better understand the vesicular pathways that may contribute to intracellular signaling and cooperate with AP‐3, we performed a vesicular siRNA screen. We identified Rab8 and Rab11 GTPases as important in IL‐6 induction upon stimulation with the TLR2 ligand Pam3 CSK4 or the pathogen, Borrelia burgdorferi ( Bb ), the causative agent of Lyme disease. These Rabs were recruited to late and lysosomal stage phagosomes and co‐transported with TLR2 signaling adaptors and effectors, such as MyD88, TRAM and TAK1, in an AP‐3‐dependent manner. Our data support a model where AP‐3 mediates the recruitment of recycling and secretory vesicles and the assembly of signaling complexes at the phagosome. Abstract : This study explores the intracellular vesicular pathways mediating the activation of toll‐like receptor 2 (TLR2). We find that the AP‐3 molecule is critical in mediating the fusion between recycling compartments and the Lyme disease‐causing Borrelia burgdorferi phagosome, contributing to TLR2 phagosomal signaling. AP‐3 is also required for the delivery of signaling molecules such as MyD88, TRAM and TAK1 to the phagosome. Therefore, AP‐3‐dependent recruitment of recycling vesicles regulates phagosomal‐dependent activation of inflammatory mediators.